2012
DOI: 10.5586/aa.2010.032
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Achene heteromorphism on progeny traits in the shaggy soldier [Galinsoga ciliata (Rafin) S. F. Blake]

Abstract: A b s t r a c tThe shaggy soldier [Galinsoga ciliata (Rafin) S. F. Blake], family Asteraceae] is an invasive species that poses a growing threat to crop production. This annual plant produces heteromorphic achenes in a capitulum type inflorescence. The objective of this study was to compare selected morphological and phenological parameters and the success of generative reproduction in plants developed from peripheral and central achenes of the capitulum. The somatic variability of G. ciliata diaspores contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The success of Galinsoga is most probably associated with its extremely efficient reproduction; even 8 to 9 weekold plant can produce 3,000 flower heads and a huge number of seeds, up to over 7,000 (Kagima, 2000). Galinsoga is also a very flexible weed because it produces heteromorphic achenes in a capitulum-type inflorescence, which probably supports survival under variable environmental conditions (Kucewicz et al, 2010). Galinsoga species occupy fields, gardens, railways and ruderal sites and may also invade seminatural habitats such as forest paths, clearings and margins in woodlands (Tokarska-Guzik, 2003Chmura, 2004;Kabuce and Priede, 2010a;Trzcińska-Tacik et al, 2010).…”
Section: Galinsoga Quadriradiatamentioning
confidence: 99%
“…The success of Galinsoga is most probably associated with its extremely efficient reproduction; even 8 to 9 weekold plant can produce 3,000 flower heads and a huge number of seeds, up to over 7,000 (Kagima, 2000). Galinsoga is also a very flexible weed because it produces heteromorphic achenes in a capitulum-type inflorescence, which probably supports survival under variable environmental conditions (Kucewicz et al, 2010). Galinsoga species occupy fields, gardens, railways and ruderal sites and may also invade seminatural habitats such as forest paths, clearings and margins in woodlands (Tokarska-Guzik, 2003Chmura, 2004;Kabuce and Priede, 2010a;Trzcińska-Tacik et al, 2010).…”
Section: Galinsoga Quadriradiatamentioning
confidence: 99%
“…In other species, Crepis aspera, C. sancta, Galinsoga ciliata, no differences in height and/or in reproductive ability were observed between the offspring of various morph types (El Keblawy, 2003;Imbert et al, 1996;Kucewicz et al, 2010). Several studies have shown that the morphological and phenological differences between plants raised from different morphs are manifested at various stages of life (El Keblawy, 2003;Kucewicz et al, 2010;Ruiz De Clavijo, 2001).…”
Section: Introductionmentioning
confidence: 86%
“…Like G. parviflora, the adult plants of Crepis aspera and Galinsoga ciliata (shaggy soldier) from different morph types showed no difference in their height (El Keblawy, 2003;Kucewicz et al, 2010). However, individuals of G. ciliata from dimorphic achenes developed at different rates, but formed homogeneous groups as regards height values at the end of their life cycle (Kucewicz et al, 2010 between individuals from peripheral and central achenes were found in Hedypnois cretica and Bidens pilosa (El Keblawy, 2003;Forsyth and Brown, 1982). Plant height is a very variable feature of individuals and is regarded as a measure of living conditions of plant populations (Moles et al, 2009).…”
Section: Synchrony Of Growth Rates Final Height and Flowering Phenologymentioning
confidence: 99%
See 2 more Smart Citations